2009
DOI: 10.1073/pnas.0810095106
|View full text |Cite
|
Sign up to set email alerts
|

The capillarity of nanometric water menisci confined inside closed-geometry viral cages

Abstract: We present an investigation of water menisci confined in closed geometries by studying the structural effects of their capillary forces on viruses during the final stage of desiccation. We used individual particles of the bacteriophage 29 and the minute virus of mice. In both cases the genomic DNA was ejected from the capsid. However, although the structural integrity of the minute virus of mice was essentially preserved, the 29 capsid underwent a wall-to-wall collapse. We provide evidence that the capillary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 27 publications
0
41
0
2
Order By: Relevance
“…S4B). We assumed the core to be fully occupied by DNA because upon desiccation the internal phage proteins were presumably ejected together with a fraction of condensed DNA (24,35). If, on the other hand, a small amount of internal phage proteins had remained inside, the fact that they have been found to give the same dielectric response as the shell proteins and occupy a small fraction of the whole viral volume would make our model a reasonable approximation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4B). We assumed the core to be fully occupied by DNA because upon desiccation the internal phage proteins were presumably ejected together with a fraction of condensed DNA (24,35). If, on the other hand, a small amount of internal phage proteins had remained inside, the fact that they have been found to give the same dielectric response as the shell proteins and occupy a small fraction of the whole viral volume would make our model a reasonable approximation.…”
Section: Resultsmentioning
confidence: 99%
“…S1 and S2), and then with 4 M guanidinium chloride (GuHCl) to force their collapse, thus avoiding the formation of a water meniscus inside (35). In transmission electron microscopy (TEM) images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, this genome can also be ejected from the otherwise intact infectious virion at physiological temperatures, again in a 3=-to-5= direction, by divalent cation depletion, in a process that leaves the 5= end of the genome firmly complexed with the particle (7). Similarly, it has been shown that during the final stages of desiccation, MVM ejects its genome from the capsid, which nevertheless remains intact, resisting collapse or disintegration (4). These observations raise the possibility that the exceptionally robust MVM particle may have specifically evolved to expose the 3= end of its genome in vivo in response to a physiological stimulus, undergoing a conformational shift that leaves the uncoated DNA associated with the intact capsid, which might then play additional roles in the viral life cycle.…”
mentioning
confidence: 99%
“…À ce jour, outre les études concernant le VIH-1, des études d'imagerie par AFM ont été réalisées sur plusieurs types de virus comme les bactériophages [27], des parvovirus [28], ou des virus plus complexes, comme le HSV (virus de l'herpès simplex) [29]. Comme en cryo-EM, la résolution de cette méthode est telle qu'il est possible d'observer les protubérances des protéines de structure de certains virus non enveloppés qui sont en général à symétrie icosaédrique, et d'en déterminer leur nombre de triangulation ainsi que leurs axes de symétrie [30].…”
Section: Resultsunclassified